2011
DOI: 10.3399/bjgp11x561249
|View full text |Cite
|
Sign up to set email alerts
|

Are physical activity interventions in primary care and the community cost-effective? A systematic review of the evidence

Abstract: BackgroundThe health and economic burden of physical inactivity is well documented. A wide range of primary care and community-based interventions are available to increase physical activity. It is important to identify which components of these interventions provide the best value for money. AimTo assess the cost-effectiveness of physical activity interventions in primary care and the community. Design of studySystematic review of cost-effectiveness studies based on randomised controlled trials of interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
0
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(171 citation statements)
references
References 31 publications
7
150
0
14
Order By: Relevance
“…Three other recent systematic reviews [101][102][103] provide evidence that interventions in primary care, including brief interventions and telephone interventions, may be effective and/or cost-effective. The review by Orrow and colleagues 103 also mainly synthesised trials with self-reported activity as the primary outcome, but included all primary care interventions with at least 12 months' follow-up.…”
Section: Cost-effectiveness Of Motivational Interviewing 'Boosters'mentioning
confidence: 99%
See 1 more Smart Citation
“…Three other recent systematic reviews [101][102][103] provide evidence that interventions in primary care, including brief interventions and telephone interventions, may be effective and/or cost-effective. The review by Orrow and colleagues 103 also mainly synthesised trials with self-reported activity as the primary outcome, but included all primary care interventions with at least 12 months' follow-up.…”
Section: Cost-effectiveness Of Motivational Interviewing 'Boosters'mentioning
confidence: 99%
“…Of the eight studies reporting on the maintenance of behaviour change, two reported a maintenance effect for at least 50% of outcomes over 3 months without the intervention. Garrett and colleagues 101 reviewed cost-effectiveness studies of physical activity interventions in primary care and found that interventions involving advice (in person, by telephone or by mail) were more cost-effective than supervised exercise interventions. This review did not examine the marginal benefit of additional interventions to maintain behaviour change as the included studies all compared a specific intervention with usual practice or no intervention.…”
Section: Cost-effectiveness Of Motivational Interviewing 'Boosters'mentioning
confidence: 99%
“…Primary care interventions based on PA are equally costeffective than drug interventions 32 and in most of the cases, could yield to more profound and sustainable gains in health than drugs. 33 In addition, existing randomised trial suggests that exercise and many drug interventions are often potentially similar in terms of their mortality benefits in the secondary prevention of cardiovascular diseases and prevention of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, community-based PA interventions have been found to be more cost-effective than supervised exercise sessions (Garrett et al, 2011). Furthermore, a broad review of community-based PA interventions concluded that these interventions are most effective when some form of personal contact for intervention delivery is included (Bock, Jarczok, & Litaker, 2014).…”
Section: Introductionmentioning
confidence: 99%